2019
DOI: 10.1108/jbim-11-2018-0333
|View full text |Cite
|
Sign up to set email alerts
|

Enticing the IT crowd: employer branding in the information economy

Abstract: Purpose The purpose of this paper is to develop an instrument to measure employer branding in the information age. Firms increasingly migrate from matter-intensive business models to information-intensive models, where value lies in information rather than the physical objects. This shift has, in turn, led to a change in employee work skills. This is particularly true in the information technology (IT) sector, where firms rely on a limited supply of skilled labor. Employer branding, a firm’s reputation as a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
(42 reference statements)
1
29
0
Order By: Relevance
“…There exists a considerable amount of research on EB, focusing particularly on external stakeholders. Past studies have explicated EB as a ‘recruitment strategy’ aimed at attracting a pool of talented applicants (Backhaus & Tikoo, 2004; Dabirian, Berthon, et al, 2019; Dabirian, Paschen, et al, 2019). With this, empirical investigations on how EB can aid an organization to exhibit positive behaviours among internal stakeholders remain scarce, particularly, in the IT context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists a considerable amount of research on EB, focusing particularly on external stakeholders. Past studies have explicated EB as a ‘recruitment strategy’ aimed at attracting a pool of talented applicants (Backhaus & Tikoo, 2004; Dabirian, Berthon, et al, 2019; Dabirian, Paschen, et al, 2019). With this, empirical investigations on how EB can aid an organization to exhibit positive behaviours among internal stakeholders remain scarce, particularly, in the IT context.…”
Section: Discussionmentioning
confidence: 99%
“…The IT industry has witnessed a sweeping change in terms of technological innovation, demographics, market disruption and competition (Dabirian, Berthon, et al, 2019; Dabirian, Paschen, et al, 2019; Gannon, 2013; Moquin et al, 2019). With the unpredictable shades of an erratic market, the Indian IT sector faces the shortage of skilled employees.…”
Section: Introductory Backgroundmentioning
confidence: 99%
“…Li and Zhang (2019) also demonstrated that SM usage effects customer loyalty and is mediated by buyers’ trust in salespersons’ integrity/benevolence and as such can indirectly improve a buyer’s loyalty. Also, as seen in the employee branding literature by Dabirian et al (2019) and Duncan et al (2019), employees participate and contribute information related to their employers on the different available SM channels. As these contributions increase, they indirectly contribute to the overall brand image and reputation of their employers, the seller organizations.…”
Section: Evaluation Of Alternativesmentioning
confidence: 99%
“…The first two articles examine the employer/employee topics within the B2 context. Dabirian et al (2019), in article seven , develop an instrument to measure employer branding value propositions for IT firms as a means to gain competitive advantage in an industry where talent is a highly competed-for resource. In article eight , Duncan et al (2019) explore brand image of B2B firms through the lens of employee reviews on social media and demonstrate the value that firms can gain from this type of “competitive intelligence”.…”
Section: Emerging Technologies and Value Creation In Business And Industrial Marketingmentioning
confidence: 99%